Transcatheter closure of hypertensive ductus with amplatzer post infarction muscular VSD occluder after percutaneous retrieval of embolized amplatzer duct occluder - Milind S Phadke; Satish Karur; Prafulla G Kerkar (Wolters Kluwer Medknow Publications, 2014)
Transcatheter closure of a large hypertensive patent ductus arteriosus is challenging with scant data about it. Even more challenging is retrieval of an embolized Amplatzer duct occluder. We report successful closure of a 12 mm large ductus with the Amplatzer muscular VSD occluder (post myocardial infarction) after percutaneous retrieval of the embolized, largest available, 16/14 mm Amplatzer duct occluder.